2018
DOI: 10.1002/cptc.201800038
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Quenching of Singlet Oxygen and Other Reactive Oxygen Species in Water: A Reliable Method for the Determination of Quantum Yields in Photochemical Processes?

Abstract: The production of singlet oxygen in aqueous solutions by photosensitizers (PS) grafted on silica was evaluated using the widely‐known singlet oxygen quencher, furfuryl alcohol (FFA). Although reliable data could be obtained when working with some of the water‐soluble PS in homogeneous solution, strong diffusion effects prevented the measurement of accurate singlet oxygen quantum yields of the silica materials. Moreover, when electron‐transfer reactions were possible and produced other reactive oxygen species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Specifically, (1) VA is excited to the singlet state ( 1 P*) and rapidly undergo intersystem crossing to the triplet state ( 3 P*). The VA in the triplet state can then participate in an electron transfer reaction with water to give the reduced radical anion, which can react with dissolved oxygen to form superoxide anion (O 2 •– ) (). Then, the O 2 •– formed will convert NO 2 or NO to nitrite (R5). (2) The excited photosensitizer generates reducing radical intermediates to directly react with NO 2 to produce HONO/NO 2 – (). ,,,, To explore the role of dissolved O 2 in the secondary formation of nitrite, we measured nitrite production from the solutions of 200 mM nitrate (AN and SN) with 5 mM VA at pH = 8 under N 2 -saturated condition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Specifically, (1) VA is excited to the singlet state ( 1 P*) and rapidly undergo intersystem crossing to the triplet state ( 3 P*). The VA in the triplet state can then participate in an electron transfer reaction with water to give the reduced radical anion, which can react with dissolved oxygen to form superoxide anion (O 2 •– ) (). Then, the O 2 •– formed will convert NO 2 or NO to nitrite (R5). (2) The excited photosensitizer generates reducing radical intermediates to directly react with NO 2 to produce HONO/NO 2 – (). ,,,, To explore the role of dissolved O 2 in the secondary formation of nitrite, we measured nitrite production from the solutions of 200 mM nitrate (AN and SN) with 5 mM VA at pH = 8 under N 2 -saturated condition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Likewise, the deactivation of 1 O 2 using L-histidine [56] and furfuryl alcohol [57] can be explained using Eqs. (13) , (14) : …”
Section: Resultsmentioning
confidence: 99%
“…Since photodecomposition proceeds in the presence of air, it was suggested that 1 is consumed for the formation of EPO, thereby indicating that compound 1 likely plays two roles, namely the generation and capture of singlet oxygen. However, the photodecomposition of 1 was suppressed in air in the presence of additives (Fig 2 ), including FFA [20], TEDA, BHT [21], and TEMP [16], which are all compounds used to detect and capture singlet oxygen. Decomposition was suppressed by the addition of these compounds, thereby indicating the involvement of singlet oxygen in the photodecomposition of 1.…”
Section: Suppression Of Dba Decomposition In the Absence Of Airmentioning
confidence: 99%
“…In particular, when TEDA was added, ~90% of 1 remained. TEDA catalytically traps singlet oxygen, while FFA, BHT, and TEMP combine with singlet oxygen and are converted to more stable compounds [20][21][22]. Since the relative concentrations of FFA, BHT, and TEMP added to 1 decrease as singlet oxygen capture progresses, the consumption of 1 is not suppressed.…”
Section: Suppression Of Dba Decomposition In the Absence Of Airmentioning
confidence: 99%